Mitigation of end zone cracks in precast prestressed concrete girders using shape memory alloys - Sun, C. Shawn; Babarinde, Oluwatobi; Kuruppuarachchi, Dinesha; Farzana, Nahid (Frontiers in Materials, 2024)
Precast prestressed concrete girders are widely used in U.S. bridge construction. With advancements in high-performance concrete and new girder designs, these girders are now capable of achieving significantly longer spans. Such spans often require deeper girders and an increased number of prestressing strands. The resulting bursting forces at the girder ends at time of prestress release may cause end zone cracking, especially horizontal web cracks, which can compromise the durability of the girders and potentially lead to rejection by bridge owners. Current practices focus on mitigating these cracks by providing adequate end zone reinforcement, but completely eliminating them remains a challenge, as girders are typically prestressed along their length only. This paper proposes an innovative approach to combat end zone cracking through the application of vertical prestressing at the girder ends using shape memory alloys (SMAs). This method involves heating prestrained SMAs at the beam ends to induce recovery stress, thus generating vertical prestress that enhances splitting resistance and reduces web cracking. The research employed a variety of NiTi SMA reinforcement, including wires, strands, and cables, demonstrating the feasibility of this method through both smallscale and full-scale beam tests. The findings suggest that properly designed vertical prestress can effectively counteract bursting forces and mitigate concrete cracking.